Decifrare la chimica invisibile: un excursus storico-epistemologico dai tubi di Crookes alla radioattività - Celestino, Teresa (Chimica nella Scuola, 2022)
The period between the last decades of the 19th century and the beginning of the 20th was characterized by extremely lively science, underpinning new subject areas in physics and chemistry. At the same time, the language of science went through a phase of great renewal. Central was the role of the discovery of radioactivity, the historical background of which is therefore extremely important for secondary school students. This phase of great progress generated collective euphoria, curiosity about paranormal phenomena and a certain aura of mysticism, as proved by theatre and film shows, reports about mediums and strange scientific-theosophical mixtures.